Sobieski palace in Lublin after the assessment of the existing condition. Restoration and modernization project = Pałac Sobieskich w Lublinie po ocenie stanu istniejącego. Projekt rewaloryzacji i modernizacji obiektu - Wrana, Jan; Fitta, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Palace, situated in Bernardyńska Street in Lublin, has a checkered history - it was, among others, mentioned in the vetting in 1661; then it was the Sobieski family's property for about 100 years. In the subsequent periods, its owners changed several times, and the object itself was repeatedly rebuilt.
Keywords: Pałac Sobieskich (Lublin); Politechnika Lubelska; tożsamość miejsca; zespół pałacowy; rewaloryzacja; modernizacja; programy unijne; Rewitalizacja miast 2014-2020; Sobieski Palace (Lublin); Technical Univesity of Lublin; place identity; modernisation of a historic building; Town Restoration Programme 2014-2020